New approach to the exact solution of viscous flow due to stretching (shrinking) and porous sheet - Azhar Ali; Dil Nawaz Khan Marwat; S. Asghar (Results in Physics, 2017)
Exact analytical solutions for the generalized stretching (shrinking) of a porous surface, for the variable suction (injection) velocity, is presented in this paper. The solution is generalized in the sense that the existing solutions that correspond to various stretching velocities are recovered as a special case of this study. A suitable similarity transformation is introduced to find self-similar solution of the non-linear governing equations. The flow is characterized by a few non-dimensional parameters signifying the problem completely. These parameters are such that the whole range of stretching (shrinking) problems discussed earlier can be recovered by assigning appropriate values to these parameters. A key point of the whole narrative is that a number of earlier works can be abridged into one generalized problem through the introduction of a new similarity transformation and finding its exact solution encompassing all the earlier solutions. Keywords: Exact solutions, New similarities, Permeable and moving sheet